Live-surgery workshop highlights microwave ablation in gynaecological minimally invasive gynaecological surgery - Ahmad, Zatul Akmar; Abdullah, Bahiyah; Asmary, Asmahany; Hashim, Erwina; Mohd Mohtar, Nur Faezza; Abdul Khalid, Thara Nur Atiqah; Zakaria, Siti Nursofiani (Faculty of Medicine, 2026)
On 3 February 2026, a Live-Surgery Workshop on contemporary minimally invasive gynaecological surgery (MIS), featuring microwave ablation (MWA) for selected cases of uterine fibroids and adenomyosis, was hosted by Hospital Al-Sultan Abdullah (HASA). With MWA gaining momentum in Malaysia, the hospital proudly embraces this milestone in uterus- preserving care.